Vibrational Spectroscopic Study and NBO Analysis On 2-Chloro-4, 6-Diamino-1,3,5-Triazine Using DFT Method - A. Lakshmi2 and A. Janaki3, V. Balachandran1, (Recent Research in Science and Technology, 2011)
In this work, we report a combined experimental and theoretical study on molecular structure, vibrational spectra, NBO analysis of 2-chloro-4,6-diamino-1,3,5-triazine(CDAT). The FT-Raman and FT-IR spectra of CDAT were recorded in the solidphase. The molecular geometry, harmonic vibrational frequencies and bonding features of CDAT in the ground state have been calculated by using density functional method (B3LYP) with standard 6-311++G** basis set. Stability of the molecule arising from hyper conjugative interactions, charge delocalization has been analyzed using natural bond orbital (NBO) analysis. All the normal modes of vibrations are assigned and calculations of total energy distribution (TED) are also performed.